Design and implementation of an appropriate motor controller to improve the range of an e-bike - Ridwan, Rafid; Oishi, Fariha Tabassum; Sadab, Md. Shahed; Rafid, Md. (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.